2010
DOI: 10.5037/jomr.2029-283x.2010.1.1.e7
|View full text |Cite
|
Sign up to set email alerts
|

Spiral Computed Tomography Based Maxillary Sinus Imaging in Relation to Tooth Loss, Implant Placement and Potential Grafting Procedure

Abstract: Objectives:The purpose of the present study was to explore the maxillary sinus anatomy, its variations and volume in patients with a need for maxillary implant placement. Materials and Methods: Maxillary sinus data of 101 consecutive patients who underwent spiral computed tomography (CT) scans for preoperative implant planning in the maxilla at the Department of Periodontology, University Hospital, KULeuven were retrospectively evaluated. The alveolar bone height was measured on serial cross-sectional images b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…This nding was in accordance with previous studies [2,25,26]. Comparably, Shahbazian et al [27] reported the symmetric morphology of the maxillary sinus in 83% of their cases, and according to Hamdy et al [28], the average linear cranio-caudal, antero-posterior, and medio-lateral measurements were almost bilaterally-matched in all cases. Based on our results, bilateral symmetry was even more common in those maxillary sinuses which extended into the canine area.…”
Section: Discussionsupporting
confidence: 91%
“…This nding was in accordance with previous studies [2,25,26]. Comparably, Shahbazian et al [27] reported the symmetric morphology of the maxillary sinus in 83% of their cases, and according to Hamdy et al [28], the average linear cranio-caudal, antero-posterior, and medio-lateral measurements were almost bilaterally-matched in all cases. Based on our results, bilateral symmetry was even more common in those maxillary sinuses which extended into the canine area.…”
Section: Discussionsupporting
confidence: 91%
“…Computerized Tomographic Scan (CT Scan) on the other hand, refers to ionizing radiation that is made up of an X-rays which can be used for image reconstruction using a computer. However, CT Scan has lower radiation toxicity and more costly compared to simple radiograph [8,9]. At about 8 months of intra-uterine life the body of the sphenoid bone is divided into two main parts namely; pre-sphenoid and post sphenoid parts.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, the posterior maxillary teeth are related to the sinus floor and the distance between them may vary from a good bony bridge to a very close approximation to the floor. In which cases, an impression of the root apices presents on the only separating thin lining mucosa [14]. Environmental factors may play a role in the etiology of this condition, which lead to pushing of the Schnederian membrane (highly reactive membrane) against cavity sides of the sinus following every patient's breath.…”
Section: Discussionmentioning
confidence: 99%